Protocolo de entrenamiento para operación de la planta de gas, Sardinata sur Ecopetrol, Tibú (2021)
The purpose of this degree work is to design the protocol for the training of the operator of the Sardinata sur Ecopetrol gas plant located in the municipality of Tibú Norte de Santander. In the gas plant, the measurement and monitoring of variables that occur in industrial processes that are related to gas pumping are carried out, such as level, pressure, flow, temperature, among others. These signals are transmitted through a control loop to the central room where they are monitored by the operator, who must make decisions regarding the orders delivered by the production. For this purpose, a series of knowledge in electronics, instrumentation, pneumatics, electricity, OSH standards and the environment is required by the plant operator who is in charge of this work. According to the above, a fairly rigorous training plan is needed that contains all the knowledge of the different processes, for which the design of the training protocol for the gas plant operator is presented, consisting of several modules that contain all the information specified in such a way that the trainee can be self-taught and develop their training on the same floor under the supervision of a suitable person to direct and evaluate the training.